Recency of migration, region of origin and women's experience of maternity care in England: Evidence from a large cross-sectional survey. (December 2018) - Henderson, Jane; Carson, Claire; Jayaweera, Hiranthi; Alderdice, Fiona; Redshaw, Maggie
Abstract: Background: In the UK, changes to legislation in 2003 regarding the free movement of people in the European Union resulted in an increase in immigration from countries that joined the EU since 2004, the Accession countries. Objective: To describe and compare the maternity experiences of recent migrant mothers to those who had been resident in the UK for longer, and to UK-born women, while taking into account their region of origin. Design: Cross-sectional national survey. Setting: England, 2009. Participants: Random sample of postpartum women. Measurements: Questionnaires asked about demographic characteristics, care during pregnancy, labour, birth and postnatally, about country of origin and, if not born in the UK, when they came to the UK. Country of origin was grouped into UK, Accession countries, and rest of the world. Recency of migration was grouped into recent arrivals (0–3 years), and earlier arrivals (4 or more years since arrival). Descriptive statistics and binary logistic regression were used to explore women's experiences of care. Stratified analyses were used to account for the strong correlation between recency of migration and region of origin. Findings: Overall, 5332 women responded to the survey (a usable response rate of 54%). Seventy-nine percent of women were UK-born. Of the 21% born outside the UK, a third were born in Accession countries. All migrants reported a poorer experience of care than UK-born women. In particular, recent migrants from the Accession countries were significantly less likely to feel that they were spoken to so they could understand and treated with kindness and respect. Conclusions: Given the rising population of non-UK-born women of childbearing age resident in the UK and the relatively high proportion from Accession countries, it is important that staff are able to communicate effectively, through interpreters if necessary. Implications for practice: The differences in clinical practice between women's home countries and the UK should be discussed so that women's expectations of care are informed about the options available to them.